STRES KERJA TERHADAP BURNOUT SERTA IMPLIKASINYA PADA KINERJA (Studi Terhadap Dosen Pada Universitas Widyagama Malang) - Satriyo, Moch; -, Survival (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study was to determine the effect of work stress on burnout and effect of burnout on performance. Effect of work stress on performance and effect of work stress on performance through burnout. Unit of analysis is a lecturer at the Widyagama University of Malang, includes professors and lecturers civil foundations. The object of research is the effect of work stress on burnout and its implications on the performance. Place research at the Widyagama University of Malang. Population of 120 faculty and determination of sample size the formula slovin, amounting to 55 lecturers. While the sampling technique using proportional random sampling. Analysis of statistical data is used to: 1) test the research instrument, through the Test Validity and Reliability Test; 2) did the classic assumption test; 3) Analysis of descriptive statistics, use the Frequency Distribution, and; 4) Analysis of inferential statistics, using Path Analysis (Path Analysis). The results showed that there are significant direct effect between Job Stress on Burnout Lecturer. Later research found significant direct effect on the performance of Burnout Lecturer. Furthermore, this study also found a significant direct effect between Job Stress on Performance Lecturer. Keyword: Job Stress, Burnout, and Performance